Teachers` Method of Teaching English Grammar at the Senior High Schools - Nurbaiti Nurbaiti; Wisma Yunita; Syahrial Syahrial; Elvina Gusman (Ta'dib, 2023)
This study aimed to find out the most frequently used method in teaching English grammar at the senior high schools of Mukomuko regency and to reveal the reasons of using the most frequently used method. An explanatory mixed method design was carried out to collect and analyze the data quantitatively and qualitatively. Three instruments were used; Questionnaire, interview, and classroom observational checklist. Thirty-one English teachers filled out the questionnaire, four teachers were selected to be interviewed, and two of them were observed. The results of this study showed; first, Situational Language Teaching was the most frequently used method in teaching English grammar at the senior high schools of Mukomuko regency. Second, the English teachers implemented the most frequently used method for four reasons; 1) to encourage the students` motivation in learning the English language, 2) to facilitate the students to achieve the learning’s objective, 3) to teach English grammar to the students contextually, and 4) to evaluate the students` understanding about the material given. Based on the results, it seemed that the English teachers picked the method of teaching grammar based on its simplicity and effectiveness to activate the EFL teaching and learning process. Moreover, the result provides teachers more insight and reference regarding to the method in teaching English grammar and applied it into their teaching process